Uncle Sam and Us: Globalization, Neoconservatism, and the Canadian State - Patten, Steve (Labour / Le Travail, 2004)
The article reviews the book, "Uncle Sam and Us: Globalization, Neoconservatism, and the Canadian State," by Stephen Clarkson.